NATIVE VERSUS NON-NATIVE ENGLISH SPEAKING TEACHERS: AN INSIGHT INTO INDONESIAN STUDENTSâ€™ VOICES - Novianti, Alviaderi (Jurnal Pendidikan Bahasa dan Sastra, 2018)
Several issues exist in determining the best English teacher for EFL students. Both native and non-native speaker teachers can succeed as English teachers. But there are always some pros and cons for both sides. This present paper intends to investigate the perspective or perception of college students towards their native English speaking teachers (NESTs) and non-native English speaking teachers (Non-NESTs) in teaching EFL. This research is a quantitative study with survey design. In gaining the data, twenty-five respondents of the 4th grade undergraduate students of the English Department in Cimahi were asked to respond the itemized statements on the questionnaire which used Likert-scales. The questionnaire itself was adopted and developed from the previous researcher with the similar problem background which was conducted in 2011. This study revealed that students have positive perceptions toward NEST and Non-NEST, although, in some circumstances, the students face several problems in the learning process. Thus, for both NEST and Non-NEST are required to handle the problems encountered by the students.Â Â